STATUS DARURAT KESEHATAN AKIBAT PANDEMI COVID-19 DALAM PERSPEKTIF HUKUM TATA NEGARA DARURAT DI INDONESIA - Fikri Hadi; Farina Gandryani (Arena Hukum, 2022)
The COVID-19 pandemic which hit Indonesia has caused problems about the national emergency status that was announced on March, 31st 2020. Several local governments has requested to grant permission for doing own lockdown. The President also opened the option to declare the civil emergency for the worst-case scenario. This research analyzes the health emergency in the Indonesian legal system and the concept of lockdown and civil emergency that caused by such outbreak. This research is a doctrinal research using conceptual, legal and statutes approach. The result shows that the health emergency has been regulated on Law number 6 of 2018 on Health Quarantine. However, due to the vacuum of norm of its technical regulations in early pandemic, policies in order to handle COVID-19 was based on BNPB degree. The lockdown concept in Indonesian Law also had two means according to Health Quarantine Law namely Regional Quarantine and Large-scale Social Restrictions. Both are the authority of central government. Besides, it is concluded that The Civil Emergency is not appropriate if it is based on a disease outbreak such as COVID-19.